Toward Improving Actuation Transparency and Safety of a Hip Exoskeleton With a Novel Nonlinear Series Elastic Actuator - Qian, Yuepeng; Han, Shuaishuai; Wang, Yining; Yu, Haoyong; Fu, Chenglong (IEEE/ASME transactions on mechatronics, 2023)
Actuation transparency and safety are important requirements in the design and control of assistive exoskeletons for individuals who suffer lower limb deficits but still maintain a certain level of voluntary motor control. In recent years, series elastic actuator (SEA) has been regarded as a promising solution for transparent actuation and safe human-robot interaction, thus SEAs are widely developed and applied in assistive exoskeletons. However, existing SEAs designed for assistive exoskeletons still lack both actuation transparency and safety because of high stiffness of the elastic element and the high mechanical impedance of the actuators. To address this problem, a novel nonlinear SEA (nSEA) is presented in this article. The optimized nonlinear series elastic element coupled with a quasi-direct drive motor creates the nSEA with low mechanical impedance, high backdrivability, and less acoustic noise. Besides, a new torque control, based on cascade PI control, is proposed for the nSEA to control the interaction torque with high accuracy and robustness. Finally, an experimental evaluation with human subjects is performed to validate the advantages of the nSEA-driven hip exoskeleton in the realization of actuation transparency and safety. The root-mean-square interaction torque in zero-impedance mode is as low as 0.051 N · m during walking conditions, leading to a negligible negative influence on the hip joint's range of motion, walking speed, and energy expenditure when wearing the hip exoskeleton.